A copper film with nano-pores on the surface, and a preparation method and application thereof
Patent Information
- Application Number
- CN202310182588.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-02-28
AI Technical Summary
Existing technologies for preparing copper thin film nanostructures suffer from high processing costs and long processing times, making them difficult to apply in flexible printed circuits, lithium-ion battery current collectors, and solar cells.
Nanopores were fabricated on the surface of a copper thin film by alternating forward and reverse pulse currents using a pulsed power supply. The formation of nanopores was achieved by controlling the pulse current density and duration.
This technology enables the low-cost and rapid fabrication of copper thin films with nanopores on their surface, improving the performance of flexible printed circuits, lithium-ion battery current collectors, and solar cells.
Smart Images

Figure CN117552060B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to the field of nanotechnology, and more specifically, to a copper thin film with nanopores on its surface, its preparation method, and its application. Background Technology
[0002] Copper is an important industrial metallic material, widely used not only as a core material for traditional conductive cables but also in electronic circuits, power batteries, and solar photovoltaic cells. In these fields, copper is primarily used in the form of thin copper films. Copper films can be processed by methods such as electrolysis, rolling, or vacuum sputtering, with thicknesses below 200 micrometers. Copper foil for electronic circuits and lithium batteries is prepared by electrolysis, possessing good conductivity, flexibility, machinability, and low processing costs. Copper foil is the preferred carrier and current collector for lithium battery anode materials, playing a role in conducting and collecting lithium battery current. The thinning of copper foil helps improve battery energy density, reducing overall battery weight while maintaining battery capacity, thereby increasing the driving range of electric vehicles; furthermore, it facilitates the development and use of flexible electronic products. In solar cells, copper is used as a seed layer material before electroplating deposition, typically prepared by vacuum sputtering. Beyond weight reduction, the fabrication of nanostructures in copper films also helps to further enhance their functionality. For example, as current collectors in lithium batteries, fabricating nanostructures on their surfaces can increase surface area, reduce local current density, and thus suppress lithium dendrite growth, improving the battery's operational stability. As electrodes in flexible electronic circuits, copper films with nanostructures can effectively improve the stability of flexible electronic products. For instance, printed circuits in flexible mobile phones typically undergo millions of folding and sliding cycles. During this process, fatigue failure of the metal film layer becomes the primary factor affecting product lifespan. Nanostructures can effectively suppress the propagation of microcracks during deformation, thereby enhancing the mechanical and electrical stability of flexible electronic products.
[0003] There are generally three main methods for fabricating nanostructures in copper thin films. The first is the direct growth of copper thin films with nanostructures using a special electrochemical deposition process (DOI:10.1002 / adfm.200701405). In this process, by controlling copper ion deposition and hydrogen evolution during electroplating, a three-dimensional, multilayered copper film with a porous structure is obtained on the substrate, with pore diameters on the order of tens of micrometers. The copper dendrite morphology increases the surface area at the nanoscale; this method requires controlled growth. The second method involves depositing copper on a substrate with a nanowire structure to prepare a nanoporous copper thin film layer (DOI:10.1002 / smll.201200674). As in the process described in the reference, nanowires with an average diameter of 100 nanometers are etched on a flexible PI substrate, followed by electrochemical deposition of copper. Since no copper is deposited where the nanowires are present, the resulting copper film possesses a nanoporous structure. The diameter of the nanopores is consistent with that of PI nanowires, averaging 100 nanometers. The above methods require a substrate with a nanostructure. The third method involves anodic oxidation to prepare copper nanowires (see DOI:10.1016 / j.jelechem.2019.113628). A copper substrate is placed as the anode in an electrolyte such as sodium carbonate, and a voltage of 3-31V is applied. After one hour, self-organized, tightly packed nanowires with diameters between 28-120 nanometers are obtained. This method has a longer preparation time. Furthermore, laser aperture (see DOI:10.1002 / adem.202000710) can prepare micropore arrays with pore sizes of tens of micrometers in copper films. This is also a process applicable to lithium-ion battery current collectors. However, the pores in copper films prepared by the above methods cannot reach the nanoscale, and the process cost is high. Summary of the Invention
[0004] The purpose of this disclosure is to provide a copper thin film with nanopores on its surface, a method for preparing the same, and its applications. This method has low process cost and short preparation time, and the prepared copper thin film can be applied in fields such as flexible printed circuits, lithium-ion battery current collectors, and solar cells.
[0005] To achieve the above objectives, the first aspect of this disclosure provides a method for preparing a copper thin film with nanopores on its surface, the method comprising the following steps:
[0006] S1. Connect the copper thin film to be processed to the first electrode of the pulse power supply, and place it in a Cu-containing environment. 2+ In the electrolyte; the electrolyte has a plate connected to a second electrode of a pulse power supply, the second electrode having the opposite polarity to the first electrode;
[0007] S2. Control the pulse power supply to alternately output positive pulse current and reverse pulse current to obtain the copper thin film with nanopores on the surface.
[0008] Optionally, the electrolyte is an acidic electrolyte with a pH value below 1.
[0009] Optionally, Cu in the acidic electrolyte 2+ The concentration is 0.1-2 mol / L.
[0010] Optionally, the copper film to be processed includes copper foil or a copper deposition film deposited on a substrate material.
[0011] Optionally, the copper deposition film deposited on the substrate material is deposited by electrodeposition, vacuum evaporation, or vacuum sputtering.
[0012] Optionally, within the pulse period of the pulse current output by the pulse power supply, the current density I of the positive pulse is... n + The absolute value of a with respect to the duration T of the positive pulse n + The integral value is greater than or equal to the current density I of the reverse pulse. n - The absolute value of b with respect to the duration T of the reverse pulse n - The integral value; where n is the number of cycles of the pulse current, and n≥2.
[0013] Optionally, the current density I of the positive pulse n + The absolute value of a is 0 < a ≤ 10ASD, and the duration T of the positive pulse is... n + The time ranges from 0.1 to 1000 ms.
[0014] Current density I of the reverse pulse n - The absolute value of b is 0 < b ≤ 10ASD, and the duration T of the reverse pulse is... n + The time ranges from 0.1 to 1000 ms.
[0015] Within each pulse cycle, I n + / I n - The absolute value of T is ≥1. n + / T n - ≥1, the total number of pulse cycles is any integer from 10 to 1000; n is the number of pulse current cycles, n≥2.
[0016] The second aspect of this disclosure provides a copper thin film with nanopores on its surface prepared using the method described in the first aspect of this disclosure.
[0017] Optionally, the thickness of the copper thin film with nanopores on the surface is 0.05-10 μm.
[0018] Optionally, the average diameter of the nanopore is 20-100 nm.
[0019] Optionally, the surface porosity of the copper thin film with nanopores is 10-50%.
[0020] Optionally, the depth of the nanopore is 50-1000 nm.
[0021] A third aspect of this disclosure provides a semiconductor device, wherein the electrodes of the semiconductor device comprise a substrate layer formed of a copper thin film having nanopores on its surface as described in the second aspect of this disclosure.
[0022] Through the above technical solution, this disclosure prepares a copper thin film with nanopores on its surface by pulse method. This method can be performed directly on the sample to be processed without growth control or on a substrate with a nanostructure. The process cost is low and the preparation time is short. The prepared copper thin film can be applied in the fields of flexible printed circuits, lithium-ion battery current collectors, and solar cells.
[0023] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description
[0024] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings:
[0025] Figure 1 This is a scanning mirror (200,000x magnification) image of the surface morphology of the copper thin film A1 prepared in Example 1 of this disclosure.
[0026] Figure 2 This is a scanning electron microscope (50,000x magnification) image of the surface morphology of the copper thin film A1 prepared in Example 1 of this disclosure.
[0027] Figure 3 This is a diagram illustrating the nanopores in the copper thin film A1 prepared in Example 1 of this disclosure.
[0028] Figure 4 This is a schematic diagram of the structure of a copper thin film A1 with nanopores on its surface, as described in Embodiment 1 of this disclosure.
[0029] Figure 5 This is a normal distribution curve of the diameter D of the copper thin film A1 prepared in Example 1 of this disclosure.
[0030] Figure 6 This is a log-normal distribution curve of the diameter D of the copper thin film A1 prepared in Example 1 of this disclosure.
[0031] Figure 7 This is a waveform diagram of a pulse waveform disclosed herein.
[0032] Figure 8 This is a waveform diagram of a pulse waveform disclosed herein.
[0033] Figure 9 This is a waveform diagram of a pulse waveform disclosed herein.
[0034] Figure 10 This is a waveform diagram of a pulse waveform disclosed herein. Detailed Implementation
[0035] The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.
[0036] The first aspect of this disclosure provides a method for preparing a copper thin film with nanopores on its surface, the method comprising the following steps:
[0037] S1. Connect the copper thin film to be processed to the first electrode of the pulse power supply, and place it in a Cu-containing environment. 2+ In the electrolyte; the electrolyte has a plate connected to a second electrode of a pulse power supply, the second electrode having the opposite polarity to the first electrode;
[0038] S2. Control the pulse power supply to alternately output positive pulse current and reverse pulse current to obtain the copper thin film with nanopores on the surface.
[0039] In this disclosure, the nanopores are randomly distributed on the surface of the copper thin film, and the nanopores can be through holes or non-through holes.
[0040] In this disclosure, the electrode plate of the second electrode connected to the pulse power supply can be elemental titanium or elemental titanium with a coating on its surface. The position of the electrode plate in the electrolyte can be any position commonly found in existing electroplating or stripping processes where the electrode plate is an anode or cathode. For example, in this application, at least one surface can face the copper film surface. Based on electroplating and stripping efficiency, the most preferred configuration is that the electrode plate has a flat surface with the largest area facing the copper film, with a certain electrolyte-filled area in between.
[0041] In addition, it should be noted that the pulse power supply of this application has an adjustment system for switching between positive and negative output. Therefore, the first electrode and the second electrode with the opposite polarity to the first electrode described above are two output sides of the pulse power supply with opposite polarities, and are not directly connected to the fixed positive and negative electrodes of the fuel cell stack. Of course, this is something that those skilled in the art can understand based on the technical concept of this application.
[0042] According to one embodiment of this disclosure, the electrolyte is an acidic electrolyte with a pH value below 1 (at room temperature); the acidic electrolyte may contain one or more of sulfuric acid, hydrochloric acid, oxalic acid and acetic acid.
[0043] According to one embodiment of this disclosure, Cu in the acidic electrolyte 2+ The concentration is 0.1-2 mol / L, of which Cu 2+ It can be derived from copper sulfate.
[0044] According to one embodiment of this disclosure, the sample to be processed includes a copper foil or a copper thin film deposited on a substrate material; further, the copper thin film deposited on the substrate material is deposited by electrodeposition, vacuum evaporation or vacuum sputtering deposition, and the specific steps are conventional in the art and are not specifically required here.
[0045] According to one embodiment of this disclosure, within the pulse period of the pulse current output by the pulse power supply, the current density I of the positive pulse is... n + The absolute value of a with respect to the duration T of the positive pulse n + The integral value is greater than or equal to the current density I of the reverse pulse. n - The absolute value of b with respect to the duration T of the reverse pulse n - The integral value is given by n, where n is the number of pulse current cycles, and n≥2. The integral value must be calculated from the start of a complete pulse cycle; therefore, n≥2. In other words, by controlling the pulse circuit, the amount of copper film plated on the surface is made greater than or equal to the amount of electrolysis within any given pulse cycle. This allows for the production of copper films with nanopores without reducing the size of the copper film material. Consequently, the processing time for pulse electroplating can be reduced, and thinner copper films can be used, further saving costs.
[0046] According to one embodiment of this disclosure, the current density I of the positive pulse n + The absolute value of a is 0 < a ≤ 10ASD, and the duration T of the positive pulse is... n +The duration is 0.1-1000ms; the current density I of the reverse pulse n - The absolute value of b is 0 < b ≤ 10ASD, and the duration T of the reverse pulse is... n + The duration is 0.1-1000ms; within each pulse cycle, I n + / I n - The absolute value of T is ≥1. n + / T n - ≥1, where the total number of pulse periods is any integer from 10 to 1000; n is the number of pulse current periods, n≥2. Using the above conditions, independently distributed nanoporous structures can be prepared.
[0047] According to one embodiment of this disclosure, the waveform of pulse processing can be characterized by a positive pulse starting and a negative pulse ending (e.g., ...). Figure 7 (As shown); positive pulse begins, positive pulse ends (as shown) Figure 8 (As shown); the reverse pulse begins, and the forward pulse ends (as shown). Figure 9 (As shown); the reverse pulse begins, the reverse pulse ends (as shown). Figure 10 (As shown).
[0048] The second aspect of this disclosure provides a copper thin film with nanopores on its surface prepared using the method described in the first aspect of this disclosure.
[0049] According to one embodiment of this disclosure, the nanopore can be a standard circle or a similar circle shape; the diameter of the nanopore is 10-100 nm, preferably 10-50 nm, and the average diameter of the nanopore is 20-100 nm, preferably 20-25 nm; when the nanopore is a similar circle shape, the diameter can be replaced by the Ferrette diameter.
[0050] According to one embodiment of this disclosure, the thickness of the copper thin film with nanopores on its surface is 0.05-10 μm, for example, 0.05 μm, 1 μm, 5 μm, 10 μm, etc. In this disclosure, the thickness of the area on the surface of the copper thin film where no nanopores are formed does not change significantly after alternating forward pulse current electroplating and reverse pulse current stripping. However, it should be noted that the copper thin film with nanopores on its surface is formed by alternating forward pulse electroplating and reverse pulse stripping of a copper deposition film or thin copper foil formed by a deposition process, using the process disclosed in this application. Its final thickness can be adjusted based on the original copper thin film by the pulse conditions of electroplating and stripping.
[0051] According to one embodiment of this disclosure, the diameters of all nanopores within a unit area of the copper thin film exhibit a log-normal distribution, wherein the unit area is 1 μm. 2 above.
[0052] According to one embodiment of this disclosure, the surface porosity of the copper thin film is 10-50%, preferably 10-30%, where "surface porosity" refers to the proportion of the total area of all nanopore openings to the surface area of the copper thin film.
[0053] By controlling the copper content during forward pulse electroplating and reverse pulse stripping of the original copper film to be treated, the thickness variation between the original copper film and the final copper film with nanopores can be further controlled, based on obtaining the surface porosity within the aforementioned range. When the copper content during electroplating and stripping is comparable, the increase in copper film thickness can be approximately equal to the increase in thickness of the copper content in the un-apertured copper film surface area where through-holes are absent. For example, when the surface porosity is 10% and the through-holes are present, the surface thickness increase rate is approximately 11%. In other words, this application can increase the copper film thickness by electroplating a portion of copper in the un-apertured areas while simultaneously forming nanopores.
[0054] However, it should be noted that the final film thickness can be controlled by adjusting the copper content of the copper film during forward pulse electroplating and reverse pulse stripping using other configuration methods. For example, when the copper content during reverse pulse stripping is greater than the copper content during forward pulse electroplating, and the difference is approximately equal to the copper content of the missing via portion, the final film thickness of the copper film with nanopores can be controlled to remain relatively unchanged. Furthermore, if necessary, the copper content during reverse pulse stripping can be further increased to make the copper film thinner while simultaneously forming nanopores.
[0055] According to one embodiment of this disclosure, the depth of the nanopore is 50-1000 nm, for example, it can be 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 200 nm, 500 nm, 1000 nm, etc. The "depth of the nanopore" refers to the distance from the opening of the nanopore to the deepest point of the nanopore.
[0056] A third aspect of this disclosure provides a semiconductor device, wherein the electrodes of the semiconductor device comprise a substrate layer formed of a copper thin film having nanopores on its surface as described in the second aspect of this disclosure.
[0057] In this embodiment, the SEM instrument model is JEOL 7800Prime; the method for testing the depth of the nanopores is to directly test the depth of the cross-section of the sample.
[0058] Example 1
[0059] The copper thin film A1 with nanopores on its surface was prepared using the following steps:
[0060] (1) A copper thin film with a thickness of 100 nm was formed on the substrate by vacuum sputtering deposition;
[0061] (2) Connect the copper thin film deposited on the substrate material in step (1) to the first electrode of the pulse power supply and place it in an electrolyte containing copper sulfate and sulfuric acid, wherein Cu 2+ The concentration is 2 mol / L, and the pH value of the acidic electrolyte is below 1 (at room temperature); the electrolyte has a titanium elemental plate connected to a second electrode of the pulse power supply, and the polarity of the second electrode is opposite to that of the first electrode;
[0062] (3) Under room temperature (25℃) conditions, the pulse power supply was controlled to alternately output forward and reverse pulse currents to obtain a copper thin film A1 with nanopores on its surface and a thickness of 100 nm; the copper thin film A1 was subjected to SEM testing, and the results are as follows. Figure 1-3 As shown, the structural schematic diagram of copper thin film A1 is as follows. Figure 4 As shown;
[0063] I n + The absolute value is 5ASD, T n + For 50ms, I n - The absolute value is 3ASD, T n - The pulse duration is 50ms, the total number of pulse periods is 100, and the pulse waveform is as follows: Figure 7 As shown, the current density I of the positive pulse n + The absolute value of a with respect to the duration T of the positive pulse n + The integral value is greater than or equal to the current density I of the reverse pulse. n - The absolute value of b with respect to the duration T of the reverse pulse n - The integral value.
[0064] The copper thin film A1 prepared in Example 1 was subjected to SEM testing, and the result was observed at 4077644 nm. 2 The SEM image shows 1355 nanopores.
[0065] Software calculations show that the diameter D of the nanopores ranges from 10 to 50 nm, with an average diameter of 24 nm; the area A of a single nanopore ranges from 50 to 1500 nm. 2 Between, the average area is 380nm 2The perimeter L of the nanopore is between 30-140 nm.
[0066] based on Figure 3 The nanopores identified in the figure, after statistical analysis, show that the diameter D of the nanopores exhibits a log-normal distribution characteristic, as illustrated in the normal distribution curve shown below. Figure 5 As shown, the log-normal distribution curve is as follows: Figure 6 As shown; ln D follows a normal distribution: lnD ~ N(3.15, 0.23).
[0067] At the aforementioned 4077644nm 2 Within the SEM image, the surface porosity of the copper thin film A1 is 12.60%.
[0068] The depth T of the nanopores is 100 nm, meaning the nanopores in the copper thin film have a through-hole structure; the increased surface area of the copper thin film with nanopores compared to the untreated copper thin film is equal to the sum of the inner wall areas of all the nanopores, A. + =∑L×T, the calculated result is 9048194nm 2 It is approximately 2.22 times the surface area of an untreated copper film.
[0069] According to Example 1 above, this invention involves periodically performing forward and reverse pulse electroplating on a 100nm thick copper thin film formed by vacuum sputtering deposition, resulting in nano-sized vias on the surface of the copper thin film, thus obtaining a copper thin film with nano-sized vias on its surface. Since the surface of the copper thin film to be treated inevitably has some widely distributed non-uniform microstructures, during the forward pulse process, the copper thin film acts as the cathode, and the raised micro-parts on the surface more easily deposit copper ions from the electrolyte, resulting in faster growth, while the recessed micro-parts grow more slowly. During the reverse pulse process, the copper thin film acts as the anode, and the entire copper thin film can be considered essentially an equipotential body, with uniform electrolytic dissolution occurring on the surface. After multiple cycles of accumulation, the originally recessed micro-parts gradually form pores, while the originally raised parts gradually thicken and connect with each other, thus forming a new surface structure with vias on the entire copper thin film.
[0070] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.
[0071] It should also be noted that the various specific technical features described in the above embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.
[0072] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.
Claims
1. A method for preparing a copper thin film with nanopores on its surface, characterized in that, The method includes the following steps: S1. Connect the copper thin film to be processed to the first electrode of the pulse power supply, and place it in a Cu-containing environment. 2+ The electrolyte contains a plate connected to a second electrode of a pulse power supply, the second electrode having the opposite polarity to the first electrode. S2. Control the pulse power supply to alternately output positive pulse current and reverse pulse current to obtain the copper thin film with nanopores on the surface; Within each pulse cycle, I n + / I n - The absolute value is ≥1. T n + / T n - ≥1, I n + The current density of the positive pulse. I n - The current density of the reverse pulse. T n + The duration of the positive pulse. T n - The duration of the reverse pulse is n; n is the number of pulse current cycles, n≥2.
2. The method according to claim 1, characterized in that, The electrolyte is an acidic electrolyte with a pH value below 1.
3. The method according to claim 2, characterized in that, Cu in the acidic electrolyte 2+ The concentration is 0.1-2 mol / L.
4. The method according to claim 1, characterized in that, The copper thin film to be processed includes copper foil or copper deposition film deposited on a substrate material.
5. The method according to claim 4, characterized in that, The copper deposition film deposited on the substrate material is deposited by electrodeposition, vacuum evaporation, or vacuum sputtering.
6. The method according to claim 1, characterized in that, During the pulse period of the pulse current output by the pulse power supply, the current density of the positive pulse is... I n + The absolute value of 'a' relative to the duration of the positive pulse. T n + The integral value is greater than or equal to the current density of the reverse pulse. I n - The absolute value of b with respect to the duration of the reverse pulse T n - The integral value; where n is the number of cycles of the pulse current, and n≥2.
7. The method according to claim 1, characterized in that, Current density of the positive pulse I n + The absolute value of a is 0 < a ≤ 10ASD, and the duration of the positive pulse is... T n + The time ranges from 0.1 to 1000 ms. Current density of reverse pulse I n - The absolute value of b is 0 < b ≤ 10ASD, and the duration of the reverse pulse is... T n - The time ranges from 0.1 to 1000 ms. The total number of pulse cycles is any integer between 10 and 1000.
8. A copper thin film with nanopores on its surface prepared by the method according to any one of claims 1-7; characterized in that, The diameters of all nanopores within a unit area of the copper thin film exhibit a log-normal distribution, where the unit area is 1 µm. 2 above.
9. The copper thin film with nanopores on its surface according to claim 8, characterized in that, The thickness of the copper thin film with nanopores on the surface is 0.05-10 μm.
10. The copper thin film with nanopores on its surface according to claim 9, characterized in that, The average diameter of the nanopores is 20-100 nm.
11. The copper thin film with nanopores on its surface according to claim 9, characterized in that, The surface porosity of the copper thin film with nanopores is 10-50%.
12. The copper thin film with nanopores on its surface according to claim 9, characterized in that, The depth of the nanopores is 50-1000 nm.
13. A semiconductor device, characterized in that, The electrodes of the semiconductor device comprise a substrate layer formed of a copper thin film with nanopores on its surface, as described in any one of claims 8-12.
Citation Information
Patent Citations
Method for preparing nano porous copper thin film material by magnetron sputtering
CN105543796A
Preparing method for ultrafine nano-porous copper film
CN108385069A
